Prevalence of postpartum depression symptoms and associated factors (Research, Society and Development, 2023)
Objective: To identify the prevalence of postpartum depression symptoms and associated factors in women who had children in the last 12 months of 2019 in the city of Montes Claros/MG. Method: Analytical and cross-sectional exploratory study, composed of 236 women who gave birth in the last 12 months of 2019. For sample calculation, a prevalence of 20% was adopted. Household interviews were conducted, and the Edinburgh Postnatal Depression Scale was applied. Descriptive analyzes and bivariate comparisons were performed using the chi-square test. In the multivariate model, the variables that presented P value